Introduction to Tuha Rawa's Musical Composition | Pengantar Karya Komposisi Karawitan Tuha Rawa - I Made Kurniawan Putra Wibawa (GHURNITA: Jurnal Seni Karawitan, 2023)
The work of Karawitan Tuha Rawa was inspired by the phenomenon of a fisherman catching fish as a livelihood. In this activity, several movements encourage the stylists, such as throwing nets, rowing, and being pierced by fish spines by challenging the waves that crash into the canoe. Becoming a fisherman is a line of descent that begins with a father, who until now has continued his father's streak. The aim is to create an innovative work originating from the source of ideas for the fisherman phenomenon by collaborating on the violin instrument in Javanese karawitan media and developing Balinese gamelan techniques, namely kotekan and ngoncang which produce different sound colours as the hallmark of the arranger. The method of creation used is ngawirasa, wacak, planning, building, ngebah. Innovativeness provides new colour accents in the work of Tuha Rawa. It offers a new repertoire to the public through innovative karawitan compositions.